2 How Material Culture Acted on the Ancient Maya of Yucatan, Mexico. Issue 1 (September 2015) - Hutson, Scott R.; Davies, Gavin; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT This paper looks at how materiality in a specific sense (e.g., aspects of raw materials) contributes to materiality in a broader sense (e.g., the mutually constitutive relations between people and things). We embark from the point that common materials, such as stone and perishable containers (baskets, gourds), shape people's social interactions and their physical sensibilities. The use of very large stones for buildings in and around Ucí, a local political center in the northern Maya Lowlands of Yucatan, Mexico, required people to draw on a large web of social relations in order to get access to the right stone and the right labor. Furthermore, hauling such stones and placing them in walls required a very literal form of physical dialogue between laborers that is otherwise quite rare, akin to carrying a couch. We believe that the closely coordinated and intimately shared physical maneuvers required to haul and place a 150 kg stone intensified the bonds between co‐actors, who were likely part of the same household. This suggests that the stability of households depends not just on what people do, but how they do these things together. Many households at two sites near Ucí—Kancab and 21 de Abril—depended heavily on baskets and gourds since pottery was scarce. Aspects of the making of these tools, such as the procurement of materials for baskets, sent people beyond their homes and into contact with many others. Thus, we argue that discussions of materials in craftwork should expand to consider the social entanglements entailed in the procurement of materials. Furthermore, we argue that the specific tactile characteristics of perishable goods such as baskets and gourds help create different kinds of people. In households with less pottery, day to day use of baskets and gourds would have inculcated non‐discursive senses of touch that rose to discursive consciousness at community wide occasions at households that served meals on pottery. Such events would have been diacritical, making participants aware of the differences between themselves. In sum, raw materials such as stone and gourds play a large role in making actors who they were and creating social networks.